2009
DOI: 10.9735/0975-5276.1.1.14-18
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of growth and production of protease by Penicillium species using submerged fermentation

Abstract: Enzymes play a vital role in the industry with a wide range of application. Agricutural waste is the maximum waste been produced in India. This Project aims at using various agricultural wastes for the production of Protease. To achieve this various research is being conducted. Various Bacterial and Fungal species are being used for the production of Protease. Penicillium species was being used in this work for the production of Protease .In this work the various components of the media were studied and were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Protease is widely distributed among microorganisms including fungi, bacteria, and actinomycetes (Ma 2013). Among fungi genera, Aspergillus, Penicillium, Paecilomyces, Rhizopus and Rhizomucor are well-known producers of proteases (Devi 2008, Sindhu et al 2009, Krishna 2009). Patil et al (2015) reported that nine different fungi concluding Cladosporium sp., Rhizoctonia sp., Aspergillus sp., Chaetomium sp., Biosporus sp., Fusarium sp., Curvularia sp., Cladosporium sp., and Colletotrichum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Protease is widely distributed among microorganisms including fungi, bacteria, and actinomycetes (Ma 2013). Among fungi genera, Aspergillus, Penicillium, Paecilomyces, Rhizopus and Rhizomucor are well-known producers of proteases (Devi 2008, Sindhu et al 2009, Krishna 2009). Patil et al (2015) reported that nine different fungi concluding Cladosporium sp., Rhizoctonia sp., Aspergillus sp., Chaetomium sp., Biosporus sp., Fusarium sp., Curvularia sp., Cladosporium sp., and Colletotrichum sp.…”
Section: Discussionmentioning
confidence: 99%
“…S. fimicola S2 and S. fimicola N6 out of the total six strains presented largest zone around the colony of fungus, so they were selected for next work. Aspergillus, Penicillium, Rhizopus, and Rhizomucor produce proteases in large quantities (Krishna et al, 2009;Sindhu et al, 2009) and are efficient over a wide range of pH (Rao et al, 1998).…”
Section: /13mentioning
confidence: 99%
“…A máxima atividade das enzimas foi observada a 25ºC, 50°C e 60°C para os isolados do gênero Aspergillus, sugerindo a presença de grupos distintos de proteases, a exemplo de Aspergillus N44. Para Penicillium N23, a temperatura ótima das proteases foi obtida a 40°C, característica diferenciada dos resultados publicados para Penicillium spp., cuja temperatura ótima de atividade proteolítica costuma ser descrita na faixa de 27°C e 30°C (KRISHNA et al, 2009 Com relação ao pH, a atividade das proteases de maiores valores foi determinada na faixa de 6,0 a 9,0. Aspergillus N34 foi o único isolado cujo pH ótimo foi levemente ácido (pH=6,0), resultado semelhante ao citado por Thichota et al (2010).…”
Section: Atividade De Proteasesunclassified